Studi Literatur Implementasi Kastrasi pada Anjing - Satria M Ndolu; Tri Utami; Yohanes T R M R Simarmata (Jurnal Veteriner Nusantara, 2023)
Castration is one of the important aspects in the management of maintain and care for animals. The purpose of this study was to determine the age of castration in small and large breed dogs, to know purpose of carrying out castration in dogs, to know the techniques of castration in dogs. This literature study is obtained from searching and collecting various library sources from Google Scholar with the help of the Mendeley application. Based on the results of the study, age is the most important risk factor for most diseases. Castration age in large breed dogs should be done at a minimum age of 15-18 months and in small breed dogs at a minimum age of 5 months because in large breed dogs castration before 1 year can cause osteosarcoma and if castration under 6 months has a significant risk factor for the emergence of a tibial plateau angle. The aim of implementing castration in dogs is to control the population, prevent aggressive behavior, roaming and congenital abnormalities, and to prevent the occurrence of diseases such as Sertoli cell tumors in dogs with cryptorchid. Dog castration techniques that can be used are open prescrotal or scrotal castration, closed prescrotal or scrotal castration, perineal castration and scrotal ablation. The open castration technique is preferred in larger dogs because the ligation can be placed directly around the vascular pedicle and provides a safer ligation. Closed castration techniques are preferred over open techniques. This method is usually performed on small or young dogs. Based on the results of open castration studies, it shows a higher complication rate than closed castration. The closed castration technique has the disadvantage that the binding is less secure because the vessel is tied while it is surrounded by the tunica and cremaster muscles attached rather than directly tied.